Peran sekolah sebagai lembaga sosialisasi dan pembentukan karakter peserta didik - Nafalina Azzahra, Rahma; Khasanah, Nur (Jurnal Pendidikan Agama Islam, 2025)
Schools are recognized as the main institutions for socialization, where interactions among school members and the teaching of cultural values take place. This article explains the function of schools as drivers of socialization in building students’ character through learning processes, teacher examples, school culture, and collaboration with parents and the community. This study is qualitative in nature, using a literature review approach that provides explanations based on various relevant studies on character education. The literature review highlights the importance of cooperation between families and schools in the character formation process. Teachers act as educators who transfer religious and national values to students, while parents serve as primary role models influencing children’s behavior. An inclusive school culture also helps deepen students’ understanding and appreciation of character values. In addition, this study identifies several obstacles in implementing character education, such as teachers’ limited understanding of character education, the absence of a specific character curriculum, limited time, and insufficient parental support. The proposed solutions include improving teacher professionalism, integrating character values into learning, strengthening partnerships between schools and families, and providing adequate policy and resource support. The findings are expected to contribute to both theoretical insights and practical implementation of character education in schools.